De-sintering of Ba5Nb4O15 ceramic and its influence on microwave characteristics. Issue 4 (April 2017) - Tsao, Chung-Ya; Tuan, Wei-Hsing; Feng, Kuei-Chih
Abstract: The sintering behaviour of a cation-deficient perovskite, Ba5 Nb4 O15, is investigated in the present study. The highest density can be achieved through pressureless sintering at 1250 °C is only 93%. A further increase in sintering temperature results in a decrease in density; for example, the density is only 82% after sintering at 1435 °C. The density decrease, de-sintering, can be related to the formation of abnormal grains ( > 1250 °C) and the reduction of niobium ions ( > 1400 °C). The permittivity of sintered Ba5 Nb4 O15 specimen shows strong dependence on density; however, the quality factor ( Qxf ) increases to 45, 000 with the increase of sintering temperature. The increase in quality factor is attributed to the ordering of cations in the perovskite structure.